Momentous Spectral Results of Sturm-Liouville Direct Problem with Generalized M-derivative - Bas, Erdal; Karaoglan, Merve (Natl Acad Sciences India, 2026)
This paper, important spectral data have been derived for the Sturm-Liouville problem with discrete boundary conditions by using the generalized \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\mathcal {M}-$$\end{document}derivative. Spectral data proposed as representation of solution for the Sturm-Liouville problem are subjected to both initial and boundary conditions, the asymptotic formulas of the eigenvalues and eigenfunctions are realized the generalized \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\mathcal {M}-$$\end{document}derivative. The primary advantage of this strong generalized \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\mathcal {M}-$$\end{document}derivative is that it includes truncated \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\mathcal {M}-$$\end{document}series, allowing us to better deal with the behavior of the topic and thanks to the extra parameter in the definition, treat it qua a generalized adaptation of another widespread local derivatives in the literature. The results obtained through the \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\mathcal {M}-$$\end{document}series defined within the generalized \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\mathcal {M}-$$\end{document}derivative used in this paper are discussed from a broader perspective. The purpose of this article is to investigate the construction of the Sturm-Liouville problem with the generalized \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\mathcal {M}-$$\end{document}derivative by using MATLAB in visual analyses.
Keywords: Direct Data; Spectral Problem; Generalized M-Derivative; Fractional Calculus